2018
DOI: 10.1148/radiol.2017162916
|View full text |Cite
|
Sign up to set email alerts
|

Precision Matters in MR Imaging–targeted Prostate Biopsies: Evidence from a Prospective Study of Cognitive and Elastic Fusion Registration Transrectal Biopsies

Abstract: Purpose To measure the precision in placement of a biopsy needle in a magnetic resonance (MR) imaging-detected target with transrectal ultrasonography (US), to document the clinical relevance of precision, and to report on the precision of cognitive and software-based registrations. Materials and Methods This prospective study was approved by the institutional review board and performed between June 2013 and September 2013. Patients provided informed verbal consent. Two cores each were obtained with cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 32 publications
(38 reference statements)
0
28
0
1
Order By: Relevance
“…258,259 To enhance adequacy, much effort has been made to improve the approach route for needle biopsy 260,261 and, in needle design, to increase core length. 255 Accuracy of needle targeting is affected by mode of imaging guidance 262 and by tip deflection, which in turn is affected by prostate size and tissue texture. 263…”
Section: Prostatementioning
confidence: 99%
“…258,259 To enhance adequacy, much effort has been made to improve the approach route for needle biopsy 260,261 and, in needle design, to increase core length. 255 Accuracy of needle targeting is affected by mode of imaging guidance 262 and by tip deflection, which in turn is affected by prostate size and tissue texture. 263…”
Section: Prostatementioning
confidence: 99%
“…FBx highlights the benefits that fusionguided procedures may offer patients; however, challenges and limitations remain. Currently, outcomes for image-guided prostate biopsy and focal ablation are highly dependent upon accurate needle placement at an exact target location [7,8,[10][11][12][13][14]. Semi-automated computer navigation and guidance allow for the registration (alignment/matching) of pre-procedural imaging (i.e, mpMRI) with real-time intra-procedural imaging (i.e, US).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted biopsy with deformable magnetic resonance/transrectal ultrasonography (MR/TRUS) image registration system was able to improve the detection of clinically significant prostate cancer (csPCa) by reducing the number of clinically insignificant prostate cancer detections compared with systematic biopsy …”
mentioning
confidence: 99%
“…More importantly, the various experts for targeted biopsy have likely reported that as long as they carry out the targeted biopsy with MR/ultrasonography image fusion, image visibility of the target in not only MRI, but also TRUS is important to improve the detection rate of csPCa . Interestingly, a deformable MR/TRUS image registration system achieved a higher precision in placement of a biopsy needle in the MRI‐detected target with TRUS …”
mentioning
confidence: 99%